Improving Sexual and Gender Minority Cancer Care: Patient and Caregiver Perspectives From a Multi-Methods Pilot Study - Kano, Miria; Jaffe, Shoshana Adler; Rieder, Stephanie; Kosich, Mikaela; Guest, Dolores D.; Burgess, Ellen; Hurwitz, Ariel; Pankratz, Vernon Shane; Rutledge, Teresa L.; Dayao, Zoneddy; Myaskovsky, Larissa (Frontiers in Oncology, 2022)
Purpose Up to 1 million lesbian, gay, bisexual, and transgender (i.e., sexual and gender minority, SGM) individuals in the United States have histories of cancer. This medically underserved population is diverse, with complex sexualities and gender identities, and distinct health concerns. SGM persons experience disproportionate risks for, and rates of, anal, breast, cervical, colorectal, endometrial, lung, and prostate cancers, in addition to cancers affecting transgender persons who have undergone sex-reassignment. SGM individuals are linked by shared experiences of stigmatization as a minority population for which little cancer research has been conducted. SGM cancer patients frequently report reluctance to seek healthcare, have poorer outcomes following diagnosis, engage in elevated risk behaviors (i.e. smoking and alcohol use) even after cancer diagnosis, have difficulty making emotional adjustment to illness, and experience higher rates of psychological distress. They report less satisfaction with cancer care, deficiencies in patient-centeredness and shared decision-making, gaps in care, and social isolation. Minority stress resulting from experiences of anti-SGM sentiment and discrimination affects cancer patients and their informal cancer caregivers. Our paper presents findings from a pilot study to identify gaps and opportunities to improve cancer care for SGM patients and caregivers at the University of New Mexico Comprehensive Cancer Center. Methods Between June 2020 and July 2021, we used a multi-methods research design informed by ecological theory to collect qualitative and quantitative data regarding cancer patient and caregiver quality of life (QoL) and experiences of cancer and survivorship care. We used PROMIS measures distributed via REDCap to assess QoL (i.e., fatigue, pain interference, pain intensity, anxiety, depression, emotional support, social isolation, and companionship), and conducted in-depth semi-structured interviews. We recruited 10 SGM cancer patients and 8 heterosexual, cisgender (H/C) patient matches, and their self-identified informal cancer caregivers (n=36, dyad total n=18). Interviews ranged from 1 to 2 hours, were audio-recorded and transcribed for analysis. The study was approved by the University of New Mexico Human Research Protections Office Institutional Review Board. Results Results of the PROMIS QoL assessments indicated that SGM patients reported greater anxiety [mean (SD) = 54.5 (8.8)] and depression [mean (SD) = 49.3 (4.8)] than H/C patients [mean (SD)=51.6 (7.5) and 45.4 (6.8) respectively], while heterosexual, cisgender (H/C) patients reported higher fatigue [mean (SD) =52.04 (8.18)] and stronger pain intensity than SGM patients [mean (SD)=48.3 (9.1) and 37.8 (9.1) respectively]. SGM patients reported higher levels of social isolation [mean (SD) = 48.3 (7.3) vs. 42.1 (7.4) for H/C patients, whereas H/C patients reported more emotional support (mean (SD) =57.5 (9.3) vs. 53.0 (6.9)] and companionship [mean (SD) = 55.2 (8.6) vs. 51.5 (11.0)]. SGM and H/C differences in caregiver QoL were most notable with regards to higher levels of fatigue [mean (SD) = 47.1 (6.0) for SGM, and 42.4 (11.5) for H/C] and companionship [mean (SD) = 55.3 (6.0) for SGM, and 50.9 (5.5) for H/C]. Qualitative interviews supported our quantitative results. SGM patients and caregivers articulated experiences of anti-SGM stigma and discrimination contributing to minority stress that influenced their initial cancer care encounters. SGM dyads had more trepidation and/or medical mistrust during initial cancer care encounters when compared to H/C patients and caregivers. SGM patients questioned care that was not culturally responsive to SGM preferences, while H/C patients were more apt to identify gaps in communication and perceived lack of clarity regarding cancer care delivery. Although SGM patients experienced high satisfaction with their cancer care once they developed trust with their providers, they discussed desires to have more direct conversations with their oncologists about their sexual orientation and gender identities and sexual health. All patients and providers in the study (SGM and H/C) appreciated their oncology care teams. All patients and caregivers relied on social networks comprised of friends and family, although SGM patients and caregivers had smaller social networks and relied less on biological family, and single SGM individuals experienced challenges accessing cancer care and struggled with social isolation. We discovered too, that all caregivers, regardless of Sexual Orientation and Gender Identity (SOGI), perceived a lack of support and information pertaining to their loved one’s treatment, side effects and best way to provide care. Conclusions This study demonstrates that prior stigmatizing experiences contribute to minority stress and medical mistrust for SGM cancer patients and their informal caregivers across the cancer care experience. Findings point to specific gaps in SGM cancer patient care, including lack of conversation about patient SOGI, inadequate staff and oncology provider SGM specific knowledge and cultural competence/cultural humility training, and insufficient patient supports for those who lack social support during cancer care treatment. Further, this study reveals inadequacies in SGM specific support, and overall support services for informal cancer caregivers. Additional research is required to develop targeted interventions to address minority stress and clinic environment concerns to improve cancer care for SGM patients. Importantly, while there were differences between SGM and H/C experiences of cancer treatment, significant similarities also emerged. Caregiver expressed consensus about the current lack of support and guidance for informal caregivers of cancer patients. Future work should focus on providing caregiver-specific resources in the clinic setting and facilitating support groups for caregivers to network with one another, as well as for tailoring SGM specific caregiver support services. Our findings highlight areas for improving cancer care for the SGM community, as well as a broader population of patients and caregivers.